Pengaruh Inovasi Dan Teknologi Pengelolaan Tanaman Dan Sumberdaya Terpadu (Ptt) Terhadap Keberhasilan Usahatani Padi Sawah (Suatu Kasus Di Kecamatan Bojongpicung, Kabupaten Cianjur) - ibrahim ibrahim; Euis Dasipah (OrchidAgri, 2023)
The Influence of Nature of Innovation and Technology of Plant and Resource Management on the Success of Rice Farming (Oryza Sativa L.) A Case in Bojongpicung Sub-district of Cianjur Regency). The purpose of this study is to determine: (1) Effect of Innovation Properties on Integrated Crop and Resource Management Technology (PTT). (2) The Influence of Integrated Crops and Resource Management Technology (PTT) to the Success of Wetland Paddy Farming (3) The Influence of Innovation and Integrated Plant and Resource Management Technique (PTT) to the Success of Rice Field Farming. This research uses survey method with its analysis unit is farmer of Integrated Crop Management and Sumbedaya Management in Bojong Picung District, Cianjur Regency. Sampling technique was done by random sampling as many as 102 respondents. The collected data was analyzed by path analysis, analytical adjusted to hypothesis test result. The results showed that the factors of Nature Innovation and Integrated Crop Management and Resource Technology simultaneously have a significant effect on Farming Success of 94%. The remaining 6% is influenced by other factors not examined in this study.